The Role of the Village Consultative Body in Development Planning in Umbulan Village, Cikeusik District, Pandeglang Regency - Jeni Minan; Defi Nuryadin; Eno Rurian (HK-Publishing, 2024)
Abstract Development is a process of orderly and natural change in welfare levels, encompassing economic, social, political, and legal aspects. The implementation of regional autonomy relies heavily on the readiness of local governments to structure their governance systems to ensure effective, efficient, transparent, and accountable development, while also fostering community participation. Development activities proceed continuously to bring about change, growth, and progress in line with demands and expectations; thus, development requires prior planning. Data collection techniques employed included observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. Data validity was verified through source and method triangulation. The research findings indicate that the role of the Village Consultative Body (BPD) in village development planning—based on a case study of Umbulan Village, Cikeusik District—manifests in three indicators: (1) discussing and agreeing upon draft village regulations with the Village Head; (2) accommodating and channeling community aspirations; and (3) overseeing the Village Head's performance. Supporting factors identified were (1) the educational background of BPD members and (2) the community; meanwhile, inhibiting factors included (1) insufficient participation of BPD members in meetings and (2) facilities. Keywords: Role of the Village Consultative Body (BPD), Development Planning